Instrumen Penilaian Holistik: Fondasi Evaluasi Hasil Belajar yang Valid dan Objektif - Ridho, Ahmad Rasyid; Sayidah, Aminatus; Mustofa, Ahmad Al (TSAQOFAH, 2026)
Learning outcomes assessment is a crucial component of the educational process because it determines the extent to which students’ competencies have been achieved. Assessment does not focus solely on the cognitive domain, which encompasses knowledge and understanding of subject matter, but also includes the affective domain related to students’ attitudes, motivation, and values demonstrated during learning, as well as the psychomotor domain that evaluates practical skills. This article conceptually examines the integration of these three domains in learning outcomes assessment as an effort to achieve holistic and comprehensive evaluation that reflects students’ overall development in intellectual, attitudinal, and skill-based aspects. This integrated assessment approach not only provides a foundation for teachers to design more effective, competency-oriented instructional strategies, but also encourages students to develop their potential optimally. The article underscores the importance of using valid, reliable, and objective assessment instruments so that evaluation results accurately and pedagogically accountably reflect students’ learning achievement.